2020
DOI: 10.3329/baj.v22i1.44938
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Recommendation for Four Crop Based Cropping Pattern: Potato- Boro- T. Aus-T. Aman Under AEZ – 11

Abstract: A field experiment on Potato-Boro-T. Aus-T. Aman cropping pattern was conducted in the High Ganges Floodplain Soil of Jashore (AEZ - 11) during 2014-2015 and 2015-2016 to find out optimum fertilizer management for intensive cropping attern, in relation to soil health.There were eight different treatments viz. T1=100% NPKSZnB (STB= Soil Test Based), T2=T1 + 25% N, T3=T1 + 25% NP, T4=T1 + 25% NK, T5=T1 + 25% PK, T6=T1 + 25% NPK, T7=75% of T1, and T8=Native fertility (control) as individual crop management. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…The native nutrient treatment produced the lowest mustard seed yield (0.91 and 0.96)t ha -1 in Jashore during the year of 2017-18 and 2018-19. Alike trend of increased yield in mustard due to added fertilizers in 3 or 4 cropping patterns was also reported by Barman et al (2019) and Saha et al (2016). Dobermann et al (2013) opined that site-specific plant nutrient management (STB in our study) can increase yield as well as nutrient use efficiency of crop rotation.…”
Section: Mustardsupporting
confidence: 86%
See 2 more Smart Citations
“…The native nutrient treatment produced the lowest mustard seed yield (0.91 and 0.96)t ha -1 in Jashore during the year of 2017-18 and 2018-19. Alike trend of increased yield in mustard due to added fertilizers in 3 or 4 cropping patterns was also reported by Barman et al (2019) and Saha et al (2016). Dobermann et al (2013) opined that site-specific plant nutrient management (STB in our study) can increase yield as well as nutrient use efficiency of crop rotation.…”
Section: Mustardsupporting
confidence: 86%
“…From the results of two years research on four crop based cropping pattern, it was observed that the highest REY (3.34 t ha -1 ) was recorded from T 6 (25% extra NPK over 100% STB dose) and lowest from T 8 . REY of mustard was 46% higher than 100% STB dose when 25% more NPK was added to it Barman et al (2020). also documented higher rice equivalent yield of mustard from 25% NPK+ 100% STB dose Mondal et al (2015).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…However, there is a lack of research on the effects of these management practices in the context of four crop based cropping systems. While there have been studies on chemical fertilizer management for four crop-based systems [ 25 , 26 ], as well as comparisons study of system productivity between four crop and three crop cropping systems [ 20 , 27 ]. Therefore, the present study aims to examine the influence of tillage and organic-based nutrient management on cropping system productivity, as well as the effects of these treatments on soil health improvement.…”
Section: Introductionmentioning
confidence: 99%
“…This newly adopted cropping system may increase farm income while creating job opportunities, alleviating poverty, and ultimately creating positive changes in the farmers' livelihoods. Reports have shown that the four crop-based cropping systems increased the rice equivalent yield up to 20-46% and the gross margin up to 30-41% over the existing lentil-jute-aman rice and boro-fallow-aman rice systems [4,5]. However, to acquire optimal performances in terms of yield, economic return, and soil health under the four crop-based cropping systems, the optimal fertilizer rate should be determined [6].…”
Section: Introductionmentioning
confidence: 99%